Peningkatan Pembelajaran berbasis Karakter melalui Gerakan Literasi Sekolah - Suryanti, Eny Wahyu; Ikawati, Any (Jurnal Likhitaprajna, 2020)
Character education is needed as an effort to improve the morale of students to become individuals who have noble character, moral, tolerant, tough, and good behavior. The role of family, school, and community in providing education greatly affects the character of students. Therefore, we need a character-based learning activity that can civilize students for good character. The school literacy movement (GLS) is a form of character building program that is able to improve students' reading and writing abilities, as well as quality and quality education. The purpose of this study is to determine the forms of school literacy movement activities. This type of research is a descriptive qualitative approach whose data is obtained from observations, interviews, and documentation. The results showed that the forms of school literacy movement activities in an effort to improve character-based learning include 3 stages, namely the habituation of literacy activities, the development of reading interest, and the implementation of literacy-based learning.